Azospirillum brasilense in corn grown single and intercropped with Urochloa in two contrasting soils - Odair Honorato de Oliveira; Gessi Ceccon; Denise Prevedel Capristo; Ricardo Fachinelli; Amanda Gonçalves Guimarães (Pesquisa Agropecuária Brasileira, 2022)
Abstract The objective of this work was to evaluate the agronomic performance of corn (Zea mays) grown single and intercropped with Urochloa ruziziensis in succession to soybean (Glycine max) inoculated with Bradyrhizobium japonicum, as well as the inoculation and reinoculation of corn with Azospirillum brasilense, in two contrasting soils. The experiment was carried out in two crop years, in a randomized complete block design, in a 2x2x3 factorial arrangement, with five replicates. The first evalauted factor was composed of the two constrasting soils: a clayey Rhodic Eutrustox and a sandy Rhodic Haplustox. The second factor was corn cultivation: single and intercropped with U. ruziziensis. The third factor consisted of the inoculation onto soybean and corn in succession, as follows: no inoculation in both crops, inoculation with B. japonicum onto soybean and with A. brasilense onto corn, and reinoculation with B. japonicum + A. brasilense onto soybean and with A. brasilense onto corn. In both crop years, the highest corn yields are observed in clayey soil with seeds reinoculated with A. brasilense. The annual reinoculation with A. brasilense results in a higher corn grain yield in the intercropping with U. ruziziensis in the clayey soil. Inoculation and reinoculation reduce corn yield losses caused by the competition with U. ruziziensis in intercropping.